Pushing partnerships: corporate influence on research and policy via the International Life Sciences Institute - Steele, Sarah (Public Health Nutr, 2020)
OBJECTIVE: There are concerns that some non-profit organisations, financed by the food industry, promote industry positions in research and policy materials. Using Freedom of Information (FOI) requests, we test the proposition that the International Life Sciences Institute (ILSI), one prominent non-for profit in international health and nutrition research, promotes industry positions. DESIGN: U.S. Right to Know filed five FOI from 2015 to 2018 covering communications with researchers at four US institutions: Texas A&M, University of Illinois, University of Colorado and North Carolina State University. It received 15 078 pages, which were uploaded to the University of California San Francisco’s Industry Documents Library. We searched the Library exploring it thematically for instances of: (1) funding research activity that supports industry interests; (2) publishing and promoting industry-sponsored positions or literature; (3) disseminating favourable material to decision makers and the public and (4) suppressing views that do not support industry. RESULTS: Available emails confirmed that ILSI’s funding by corporate entities leads to industry influence over some of ILSI activities. Emails reveal a pattern of activity in which ILSI sought to exploit the credibility of scientists and academics to bolster industry positions and promote industry-devised content in its meetings, journal and other activities. ILSI also actively seeks to marginalise unfavourable positions. CONCLUSIONS: We conclude that undue influence of industry through third-party entities like ILSI requires enhanced management of conflicts of interest by researchers. We call for ILSI to be recognised as a private sector entity rather than an independent scientific non-profit, to allow for more appropriate appraisal of its outputs and those it funds.